Comparison of effects between core stability training and sports massage therapy among Elite weightlifters with chronic non-specific low back pain: A randomized cross-over study - Leonard Henry Joseph (2018)
© 2018, Asian Journal of Sports Medicine. Background: Lumbopelvic stability training (LPST) andmassage therapy are common therapies used for pain reduction and management of low back pain. However, the effects of LPST and sports massage therapy (SMT) for management of chronic non-specific low back pain (CLBP) among elite weightlifters have never been studied before. Objectives: The current study investigates the therapeutic effects of LPST and SMT on pain intensity (PI), pain pressure threshold (PPT) and tissue blood flow (TBF) among elite weightlifters with CLBP. Methods: A total of 16 female athletes training for the international and Olympic weightlifting competitions participated in a randomized balanced cross-over study. The athletes were randomized into three sessions of LPST and SMT with a time interval of 24 hours within sessions and a wash out period of 4 weeks between the sessions. The PI, PPT and TBF were measured before and after each session repeatedly in both groups of interventions. The changes in the PI, PPT and TBF within and between the groups were analysed using repeated measures analysis of variance [ANOVA]. Results: The results demonstrated a reduction of PI (P = 0.01), increase in PPT (P = 0.01) and improvement of TBF (P = 0.01) among the participants in both groups of interventions. The SMT group showed a trend of greater therapeutic benefits when compared to LPST group especially in PI (P = 0.001). Conclusions: The findings suggest positive evidence on the therapeutic effects of LPST and SMT for management of CLBP among elite weightlifters with improvement in PI, PPT and TBF. Coaches, clinicians, and athletes may consider LPST and SMT as useful interventions for management of CLBP among elite weightlifters.